A Socio-Juridical Analysis of Law No. 1 of 1974 Regarding the Phenomenon of Unregistered Marriage in Sianjo-Anjo Meriah Village, Gunung Meriah District, Aceh Singkil Regency - Azhima P, Annisa Rizqa; Misran; Husnul, Muhammad (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2025)
This article discusses the analysis related to the implementation of Article 2 of Law Number 1 of 1974 concerning Marriage, which regulates the validity of marriages conducted according to the laws of each religion and the necessity of marriage registration. However, in some cases occurring in the village of Sianjo-Anjo Meriah, Gunung Meriah Subdistrict, Aceh Singkil Regency, cases of unregistered marriages (nikah siri) have been found, which were not registered at the Office of Religious Affairs (KUA). This study seeks to analyze the perspectives of the local community and village administration regarding nikah siri, and to further assess the legal certainty and effectiveness of protecting the rights of wives and children in the context of unregistered marriages at the Gunung Meriah KUA, as well as its implications for Article 2 of Law No. 1 of 1974 on Marriage and Islamic law. The research employs an empirical (socio-legal) method with a case and statute approach. Data were collected through in-depth interviews with village officials and community leaders, alongside analysis of judicial decisions. The findings of this study reveal that the practice of unregistered marriage (nikah siri) in Sianjo-Anjo Meriah Village stems from social and administrative factors. Although such marriages are religiously valid, they are not legally recognized by the state due to the absence of official registration at the Office of Religious Affairs (KUA). Consequently, wives and children are deprived of legal protections that should be guaranteed by the state. Therefore, intensive legal education, simplified access to marriage registration, and encouragement for couples who have entered into nikah siri to file for marriage validation (isbat nikah) at the Singkil Sharia Court are essential to ensure formal legal recognition.